Current Biomedical and Diagnostic Applications of Gold Micro and Nanoparticles - Pohanka, Miroslav (Mini Reviews in Medicinal Chemistry, 2021)
Production of particles and their adaptation in the pharmacology became an object of interest, and they are the currently introduced therapies based on the use of micro and nanoparticles. The use of gold particles is not an exception. This review has focused on the application of gold micro and nanoparticles in pharmacology and biomedicine. The particles can be used for diagnosis respective theranostic of cancer, rheumatoid arthritis and as antimicrobial means. Besides these applications, specifications of gold, gold particles, and colloidal gold manufacturing and their comparison with the solid gold, are described as well. This review is based on a survey of actual scientific literature.
Keywords: hyperthermia